The Role Of Land Deed Making Officials (Ppat) To Prevent Agricultural Land Conversion For Food Security In Madiun Regency - Mirnasari Putri, Cicilia; Sentot Sudarwanto, Albertus (International Journal of Educational Research & Social Sciences, 2023)
To find out the role of land deed making officials (PPAT) in agricultural land conversion policies in Madiun Regency and find out the factors that cause agricultural land conversion in Madiun Regency and what are the legal consequences. This research uses an empirical juridical approach or Socio Legal Research. The research approach used in socio-legal research uses an interdisciplinary approach. The research specification that the author uses is the descriptive research specification of the analysis. The results of the research obtained are that the role of Land Deed Making Officials (PPAT) in providing assistance in managing agricultural land conversion is an implementation of the provisions of Article 7 paragraph (1) of Government Regulation Number 24 of 2016 amending Government Regulation Number 37 of 1998 concerning Regulations of Land Deed Making Officials. In the provisions of the article, it is explained that the Land Deed Making Officer (PPAT) is guided by the Regulation of the Head of the National Land Agency Number 2 of 2011 concerning Guidelines for Land Technical Considerations in the Issuance of Location Permits, Implementation of Location Permits, and Land Use Change Permits and other related laws and regulations. Factors that cause agricultural land conversion in Madiun Regency and its significant legal consequences are factors such as the age of farmers and the level of dependence of farmers on food agricultural land have not significantly affected the level of conversion of agricultural food land in Madiun Regency. Asee the function of agricultural to non-agricultural land in the Madiun Regency area.